2012
DOI: 10.1155/2012/215810
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Features of Superficial and Deep Fibromatoses in the Adult Population

Abstract: The fibromatoses are a group of benign fibroblastic proliferations that vary from benign to intermediate in biological behavior. This article will discuss imaging characteristics and patient demographics of the adult type superficial (fascial) and deep (musculoaponeurotic) fibromatoses. The imaging appearance of these lesions can be characteristic (particularly when using magnetic resonance imaging). Palmar fibromatosis demonstrates multiple nodular or band-like soft tissue masses arising from the prox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
71
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 91 publications
4
71
1
1
Order By: Relevance
“…In a previous study (9), the maximum standardized uptake values (SUV max ) of the desmoid tumors ranged from 3.4 to 5.4, which is similar to the values found in our study (mean 3.7, 2.4-4.5). Our study demonstrated that the mean SUV max of the desmoid tumors was significantly lower than that of the malignant tumors.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In a previous study (9), the maximum standardized uptake values (SUV max ) of the desmoid tumors ranged from 3.4 to 5.4, which is similar to the values found in our study (mean 3.7, 2.4-4.5). Our study demonstrated that the mean SUV max of the desmoid tumors was significantly lower than that of the malignant tumors.…”
Section: Discussionsupporting
confidence: 90%
“…Fibromatosis can be classified according to its anatomical location into superficial and deep fibromatosis, which show different genetic backgrounds and clinical behavior (9,16,17). Superficial fibromatosis arises from fascia or aponeuroses in the extremities including palmar, plantar, penile and knuckle pad locations and usually exhibits less symptomatic and slow-growing features compared to deep fibromatosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Selective fasciotomy is the treatment of choice. 23,24 Excision of these lesions reveals a collection of small nodules within the subcutis and aponeurosis, with a yellow-tan appearance for younger lesions and a gray-white appearance for older ones. This agedependent difference in appearance reflects the tumor composition on light microscopy, further illustrated in Figure 7.…”
Section: Palmar-plantar Fibromatosesmentioning
confidence: 99%